'What research was carried out on this vaginal mesh?' Health‐related concerns in women following mesh‐augmented prolapse surgery: a thematic analysis. (21st June 2020) - Izett‐Kay, ML; Lumb, C; Cartwright, R; Kupelian, AS; Cutner, AS; Jackson, S; Price, N; Vashisht, A
Abstract : Objective: To understand health‐related issues in women following mesh‐augmented prolapse surgery. Design: Inductive thematic analysis of free‐text comments from participants in a cross‐sectional study of laparoscopic mesh sacrohysteropexy. Setting: Tertiary urogynaecology centres, United Kingdom. Population: Women who underwent laparoscopic mesh sacrohysteropexy by surgeons based at two tertiary urogynaecology centres between 2010 and 2018. Methods: A total of 1766 potential participants were contacted by post and invited to complete paper, online or telephone questionnaires containing a free‐text comments section. Of 1121 participants (response proportion 63.5%), 752 (67.1%) provided such comments. These were analysed with a six‐stage inductive thematic analysis, using NVivo 11® software. Main outcome measures: Themes developed from free‐text comments. Results: Following familiarisation, 29 codes and 189 sub‐codes were identified. These defined six themes: pelvic floor symptoms, health status, treatment success, mesh, pain and care received. The majority of comments centred on the first of these six themes. There were concerns about mesh use and a desire for more information. A range of pain symptoms were mentioned, often associated with pelvic floor symptoms, prolapse surgery or mesh. Conclusions: Despite the mesh controversy, pelvic floor symptoms and their impact on quality of life remain the principle concern of women following mesh‐augmented prolapse surgery. There is a need for quality, accessible and evidence‐based information sources for those women with concerns, and for those considering such surgery in the future, particularly regarding mesh safety and postoperative recovery. The relationships between pain, prolapse, mesh and pelvic floor surgery require further study. Tweetable abstract: Following mesh‐augmented prolapse surgery, pelvic floor symptoms remain women's main focus; pain deserves further research. Tweetable abstract: Following mesh‐augmented prolapse surgery, pelvic floor symptoms remain women's main focus; pain deserves further research.